ESPGHAN and NASPGHAN Report on the Assessment of Exocrine Pancreatic Function and Pancreatitis in Children. (July 2015) - Taylor, Christopher J.; Chen, Kathy; Horvath, Karoly; Hughes, David; Lowe, Mark E.; Mehta, Devendra; Orabi, Abrahim I.; Screws, Jeremy; Thomson, Mike; Van Biervliet, Stephanie; Verkade, Henkjan J.; Husain, Sohail Z.; et al.
Abstract : ABSTRACT: The purpose of this clinical report is to discuss several recent advances in assessing exocrine pancreatic insufficiency (EPI) and pancreatitis in children, to review the array of pancreatic function tests, to provide an update on the inherited causes of EPI, with special emphasis on newly available genetic testing, and to review newer methods for evaluating pancreatitis.